The human medial temporal lobe represents memory items in their ordinal position in both declarative and motor memory domains. - Ainsley Temudo; Nina Dolfen; Bradley R King; Genevieve Albouy (PLoS Biology)
Memory systems in humans are less segregated than initially thought as learning tasks from different memory domains (e.g., declarative versus procedural) can recruit similar brain areas. However, it remains unclear whether the functional role of these overlapping brain regions - and the hippocampus in particular - is domain-general. Here, we test the hypothesis that the hippocampus encodes and preserves the temporal order of sequential information irrespective of the nature of that information. We used multivariate pattern analyses (MVPA) of functional magnetic resonance imaging (fMRI) data acquired during the execution of learned sequences of movements and objects to assess brain patterns related to procedural and declarative memory processes, respectively. We also tested whether the hippocampus represents information about temporal order of items (here movements and objects in the motor and declarative domains, respectively) in a learned sequence irrespective of their nature. We also examined such coding in brain regions involved in both motor (primary and premotor cortices) and object (perirhinal cortex and parahippocampus) sequence learning. Our results suggest that hippocampal and perirhinal multivoxel activation patterns do not carry information about specific items or temporal position in a random series of objects or movements. Rather, these regions code for the representation of items in their learned temporal position in sequences irrespective of their nature (i.e., item-position coding). In contrast, although all other ROIs showed evidence of item-position coding, this representation could - at least partially - be attributed to the coding of other information such as position information. Altogether, our findings indicate that regions in the medial temporal lobe represent the temporal order of sequential information similarly in both the declarative and the motor memory domains. Our data suggest that these regions contribute to the development of item-position maps that might provide a cognitive framework for sequential behaviors irrespective of their nature.